(untitled) (Bangladesh Medical Journal, 2017)
Regression of ventricular hypertrophy is the restoration of normal ventricular structure and physiology after the hypertrophy has developed. It has been clearly demonstrated that once left ventricular hypertrophy (LVH) is diagnosed, it represents a strong blood pressure independent risk factor for cardiovascular morbidity and mortality.This prospective observational study was carried out in Department of Cardiology, BSMMU, Dhaka to compare the effectiveness of different anti-hypertensive agents in reducing left ventricular hypertrophy (LVH) in hypertensive Bangladeshi population involving 95 patients with clinically diagnosed hypertension. The duration of study was from July 2005 to Tune 2008. Out of these 95 patients, 20 were included in beta-blocker(BB) group, 14 in angiotensin converting enzyme inhibitor(ACEi) group, 20 in beta-blocker(BB) + diuretic(DD) group, 14 in angiotensin converting enzyme inhibitor(ACEi) + diuretics(DD) group, 13 in beta-blocker(BB) and angiotensin enzyme inhibitor(ACEi) group and 14 in beta-blocker(BB) + angiotensin converting enzyme inhibitor(ACEi) + diuretic(DD) group. patients were followed-up at 8 weeks, 6 months, 1 year and at 2 years. A baseline M-mode echocardiography was done to document LVH. Among three groups of anti-hypertensive drugs, angiotensin converting enzyme inhibitor alone has been found to be most effective as compared to beta blockers when used alone than in combination groups (Beta blocker plus ACEi plus Diuretics or Beta blocker plus ACEi). Although, statistically not significant, a clear benefit has been shown in all groups in terms of LVH regression. Bangladesh Med J. 2016 Sep; 45 (3): 156-159